Rumor has it - Rambo, Cat (Rambo, Cat. Disco space opera, 2024)
"The crew of the You Sexy Thing navigates the aftermath of facing down a pirate king and the relationships that they have created with one another in Cat Rambo's action adventure science fiction Rumor Has It, the third book in the Disco Space Opera. The crew of the You Sexy Thing have laid a course for Coralind Station, hoping the station's famed gardens will provide an opportunity to regroup, recoup, and mourn their losses while while finding a way to track down their enemy, pirate king Tubal Last. All Niko wants to do is pry their insurance money from the bank and see if an old friend might be able to help them find Last. Unfortunately, old friends and enemies aren't the only unreliable elements awaiting her and the crew at Coralind. Each will have to face themselves-the good and the bad-in order to come together before they lose everything. The Disco Space Opera You Sexy Thing Devil's Gun Rumor Has It"--